STUDI GEOKIMIA AIR PANAS AREA PROSPEK PANASBUMI GUNUNG KENDALISODO KABUPATEN SEMARANG, PROVINSI JAWA TENGAH - Yoga Aribowo; Heri Nurohman (TEKNIK, 2012)
Fluid geochemistry is a useful method to analyse lateral and vertical processes and trends in a geothermalsystem, just like a blood and urine analysis to determine the functions of internal organs in human body. Fluidsgeochemistry study in Kendalisodo Geothermal Prospect has conducted to get information about type andcharacteristics of fluids, to predict reservoir temperature, and sub surface hidrogeochemical cycle model.From fluids geochemistry analysis, the most significant constituent is HCO3, and thus all fluids classified intobicarbonate water. Based on gethermometry analysis, the average reservoir temperature calculated is about175oC and classified into medium enthalpy system.